Analysıs of Offıcıal Internet Sıtes of Sport Clubs In Terms of Socıal Medıa and Marketıng Communıcatıon: A Study on Turkısh and German Sport Clubs - Erkan Faruk Şirin; Ali Sevilmiş (Selcuk University, 2019)
Becoming widespread of internet use, advantages web has, compared to traditional environment, and purchaser tendencies in marketing communication have made web sites a potential social media communication and marketing tool for sport clubs. The main aim of this study is to evaluate official internet sites of soccer clubs of Super League İlhan Cavcav Season and Bundesliga in Germany in terms of social media communication and marketing communication and reveal the similarity and difference between both league by means of content analysis method. Internet site of a total of 36 sport clubs in both leagues were evaluated. During analysis of the data, MAXQDA qualitative data analysis software was used. According to the results of the study, while social network applications (Facebook, Twitter, etc.) in the official web sites of Turkey  and Germany  sport clubs show similarity, instant messaging applications (Snapchat), documents follow system (subscribe to RSS) and motion  videos (Giphy) or blog accessing tools were seen to be given place in German clubs. In large majority of German clubs, while official internet sites include multiple language options, in Turkey, there is multiple language option in the internet site of a few number of clubs. In addition, Turkish sport clubs use marketing communication channels in similar to traditional marketing activities, and there are differences between the clubs taking place in both leagues in terms of the use of direct communication with customers through these channels (answering the questions about, comments about product, etc.), direct marketing (information about filtering detail, cargo information, safe payment, order follow, and product return), and sale development (favorite/ the most sold product, personal product design, seasonal opportunities, etc.).